A Planar Monopole Uwb Antenna With Partial Ground Plane For Retransmission-Based Chipless RFID - Hossain, A K M Zakir; Indra, Win Adiyansyah; Jamil Alsayaydeh, Jamil Abedalrahim; Herawan, Safarudin Gazali (Intelligent Network and Systems Society, 2021)
In this article, a microstrip-feed planar monopole ultra-wide band (UWB) antenna is proposed for the chipless RFID (CRFID) tag-reader systems with the intension to reduce the size of the tag. This antenna is keyhole shaped and small in size of 32 × 20 mm2 compared with other existing antennas in the retransmission-based chipless CRFID system. The partial ground plane technique is applied here to obtain the bandwidth of 6.81 GHz within the UWB frequency spectrum. The results show it is suitable for both identification and sensing application in the retransmission-based CRFID. The antenna has a good omni-directional radiation pattern with realized gain up to 4 dBi and the realized gain to antenna size ratio goes as high 0.39/cm2 which is comparatively higher than the other existing antennas in retransmission-based CRFID. The other feature of this antenna is it has the radiation efficiency up to 99% whereby it never goes below 96% throughout the working bandwidth and the measured antenna efficiency goes as high as 95%. Furthermore, to check the suitability to apply in CRFID sensor application, the proposed antenna has been realized on three flexible substrates of polyimide, PET and paper, and very little deviations are found compared to the rigid Rogers RT 3003 substrate in terms of S11, realized gain, efficiency and radiation pattern which is a proof of robustness of the design. This proposed antenna will motivate the researcher to develop a smaller sized UWB CRFID tags.